A Study on the Factors Influencing Employee Behaviors on Organization Performance in Malaysia’s Airline Industry - Fahmi, Salim Said (2011)
The background of the research, the scope of study, and significance of the research is not left out leading to the main objective of this study. To have foundation knowledge on the topic the researcher equipped himself by reading various journals and books on issues related to Factors influencing employee behaviors on organization performance in Malaysia’s Airline industry.